CPR during COVID-19: Use of Expert-driven Rapid Cycle Deliberate Practice to Implement PALS Guidelines. Issue 1 (28th January 2021) - Nichols, Blake E.; McMichael, Ali B.V.; Volk, A. Paige Davis; Bhaskar, Priya; Bowens, Cindy Darnell
Abstract : Introduction: The American Heart Association (AHA) and other national institutions have endorsed modifications to resuscitation guidelines given the risk of healthcare workers' (HCWs) exposure to COVID-19. Institutional implementation of the COVID-19-focused guidelines requires both proof of feasibility and education of HCW. Pediatric critical care medical directors at The University of Texas Southwestern/Children's Health System of Texas (UTSW/CHST) created a guideline for the resuscitation of COVID-19 patients. The simulation team used in situ simulation to demonstrate guideline feasibility and to create educational materials. Methods: A UTSW/CHST guideline incorporated COVID-19-focused AHA and other national organizational recommendations to fit the institutional needs. A high-fidelity in situ simulation helped test the feasibility and optimize the UTSW/CHST guideline. We developed a novel form of rapid cycle deliberate practice (RCDP), expert-driven RCDP, in which all simulation participants are experts, to debrief the simulation. Results: In situ simulation with expert-driven RCDP demonstrated guideline feasibility in the resuscitation of a COVID-19 patient while balancing the protection of HCW. Expert-driven RCDP allowed for real-time alterations to the guideline during the simulation event. Video recording and dissemination of the simulation allowed for the education of over 300 staff on the new recommendations. Conclusions: High-fidelity in situ simulation with expert-driven RCDP created a rapid consensus among expert critical care providers to develop the UTSW/CHST guideline and quickly adopt the new AHA recommendations. This debriefing method helped minimize the risk of HCW exposure by minimizing the number of required participants and time for simulation. We recommend using this distinctive, expert-driven RCDP debriefing method for expeditious testing of COVID-19-focused processes at other institutions. Video Abstract available at: [link forthcoming]